Forearm rotational motion adaptations among baseball pitchers and position players - Laudner, K. G.; Lynall, R.; Williams, J. G.; Meister, K. (Journal of Athletic Training, 2012)
Context: Due to the repetitive nature of the baseball throwing motion, many chronic adaptations have been identified in the throwing shoulder of baseball players. However, little research has investigated what adaptations may occur in forearm rotation among and between baseball pitchers and position players. Objective: To determine the withingroup and between-group range of motion (ROM) differences in forearm pronation, supination, and total arc of motion in a group of baseball pitchers and a group of position players. Design: Cross-sectional. Setting: Athletic training room. Participants: Fifty professional baseball pitchers (age=22.1±2.2years, height= 188.5 ±5.7 cm, mass=87.4±8.7 kg) and 43 position players (age=22.9±4.7 years, height =183.8±5.1 cm, mass= 86.7 ±7.2 kg) volunteered to participate. All participants had no recent history (past 2 years) of upper extremity pathology or any previous surgery. Interventions: We measured bilateral elbow pronation, supination, and total arc of motion using a digital inclinometer. We used 2-tailed t tests with a Bonferroni correction (p<.004) to determine if any differences existed between and within the pitchers and position players. Main Outcome Measures: Dependent variables included forearm pronation ROM, supination ROM, and total arc of motion. Results: Pronation, supination, and total arc of motion for the dominant and non-dominant arms of the pitchers were 72.5°±8.1°, 82.5°±6.5°, 154.9°±11.4° and 76.4°± 7.7°, 82.6°±5.5°, 159.0°±10.9°, respectively. Pronation, supination, and total arc of motion for the dominant and non-dominant arms of the position players were 70.3°±8.0°, 81.6°±7.2°, 152.0°±9.8° and 72.6° ±5.6°, 81.4°±6.1°, 154.0°±7.6°, respectively. There were no significant differences between the pitchers and position players for either forearm pronation (p>.01), supination (p>.30), or total arc of motion (p>.01). However, the pit-chers did have significantly less pronation ROM (p=.001, effect size=.48) and total arc of motion (p=.001, effect size=.36) in their throwing elbow compared to their non-throwing elbow. There was no signi-ficant difference bilaterally for supination (p=.88) among the pitchers. The position players had a significant difference in their bilateral total arc of motion (p=.001, effect size=.20), but no differences in pronation (p=.07) or supination (p=.82). Conclusions: The significantly less amount of forearm pronation in the throwing arm of pitchers may occur due to the large eccentric forces produced by the supinator muscles as the elbow pronates during the follow-through and deceleration phases of the throwing motion. The accumulation of these eccentric forces may result in shortened supinator muscle length and a subsequent decrease in pronation ROM. Although both pitchers and position players had a statistically significant decrease in total arc of motion in the throwing elbow compared to the non-throwing elbow, the small effect sizes indicate these differences may not be clinically significant. These forearm ROM adaptations should to be taken into consideration in the prevention, evaluation, and treatment of elbow injuries among baseball players.